Development and evaluation of training programs to improve health checkup recommendation materials - Ogawa, Runa; Ishikawa, Hirono; Fukuda, Yoshiharu (Frontiers in Public Health, 2025)
BackgroundHealth communication materials must be easily understood by the target readers. Although numerous efforts have been made to recommend preventive services, the training of practitioners to create effective recommendation materials is insufficient. This study verifies whether the training provided to practitioners could lead to improvements in the recommendation materials using a checklist based on the suitability assessment of materials (SAM).MethodsThis study targeted the public health insurers in Tokyo. Individual and group training was provided to improve the recommendation materials of specific health checkups using a checklist with reference to the SAM. The materials (flyers, postcards, leaflets, etc.) created by the insurers were evaluated by six randomly assigned evaluators. A suitability score indicating the appropriateness of the material was calculated using an evaluation manual to verify the improvements in the materials before and after the training.ResultsOf the 49 insurers who participated in the training, 31 evaluated the materials both before and after the training. The mean suitability score [standard deviation] increased from 48.6 [7.9] before training to 51.6 [8.7] after training, although the difference was not statistically significant (p = 0.09). However, statistically significant increases were observed in four items: information essential for undergoing health checkups, clear titles and captions that explain graphic content, consistent and readable layout, and sufficient margins and line spacing.ConclusionSAM-based training led to limited improvements in the recommendation materials created by insurers. Providing more thoughtfully designed training to insurers is expected to increase effective health communication materials that encourage recipients to take action.